Eigenvalues homogenization for the fractional p-Laplacian - Ariel Martin Salort (Electronic Journal of Differential Equations, 2016)
In this work we study the homogenization for eigenvalues of the fractional p-Laplace operator in a bounded domain both with Dirichlet and Neumann conditions. We obtain the convergence of eigenvalues and the explicit order of the convergence rates when periodic weights are considered.